Sistem Monitoring dan Evaluasi Kinerja Dosen Menggunakan Metode Multi Factor Evaluation Process - Heriyan, Dina Yulina; Sari, Eka Yulia; Niswandi, Muhammad (Proceedings Series on Physical & Formal Sciences, 2023)
Monitoring and evaluating the performance of lecturers at the Faculty of Engineering, Tamansiswa Bachelor Wiyata University, the system that has been running has experienced many problems with the increasing number of active students and limited human resources. The evaluation of the learning questionnaire is filled out through the Google Form and the lecturer's data performance is processed using software such as Microsoft Office Excel or the like. In this study the aim was to produce a system that could support learning monitoring and evaluation activities in measuring the level of lecturer performance. The system is needed to process data as a tool to input and report on monitoring and evaluating lecturer performance. The method applied is the Multi Factor Evaluation Process (MFEP) using four criteria, namely pedagogic, professional, personality and social competence. Based on the results of the tests that have been carried out, the lecturer performance monitoring and evaluation system can provide decisions in the form of lecturer performance levels. The system can be used at several user levels, namely faculty academics, heads of study programs and Gugus Mutu Prodi (GMP) in assessing or measuring lecturer performance.